One-dimensional ScGa3 (ZnO) n superlattice nanowire and preparation method thereof
Doping Sc and Ga elements on ZnO nanowires by high-temperature solid-state diffusion method, one-dimensional ScGa3(ZnO)n superlattice nanowires were prepared, which solved the problem of lack of transition element doping in the prior art and realized the material High purity and unique properties have expanded its potential in electronic devices.
Patent Information
- Application Number
- CN202411326311.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The lack of research on transition element-doped superlattice nanowires in the prior art has limited the development and application of material properties.
Using a three-step high-temperature solid-state diffusion method, ZnO nanowires are coated with ScGa-ZnO precursor solution and heat treatment is performed at high temperature to prepare one-dimensional ScGa3(ZnO)n superlattice nanowires to achieve uniformity of Sc and Ga elements. Doping and reaction.
The ScGa3(ZnO)n superlattice nanowire with high purity and unique physicochemical properties has been successfully constructed, which has improved the electronic structure and optical properties, and has potential applications in light-emitting devices and liquid crystal displays.
Smart Images

Figure CN119208465A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of superlattice nanowire preparation, and in particular to a one-dimensional ScGa3(ZnO) n Superlattice nanowires and methods for preparing the same. Background Art
[0002] As a wide bandgap semiconductor material, ZnO has the remarkable characteristics of excellent thermal conductivity, low dielectric constant, high breakdown electric field and high electron saturation rate. Compared with Si, GaAs, SiC and GaN materials widely used in the industry, ZnO exhibits more outstanding radiation resistance. This feature not only enables it to work stably in high-temperature environments, but also greatly increases its potential in the development of high-frequency, high-power, high-temperature and radiation-resistant semiconductor devices. Therefore, ZnO is undoubtedly a semiconductor material with broad prospects.
[0003] In 1968, L.Esaki and R.Tsu, outstanding scientists at IBM Laboratories in the United States, first proposed the concept of superlattice. This milestone discovery not only marked a major advancement in the field of materials science, but also led to a new era of studying superlattice and quantum mechanical effects at a new physical scale. Superlattice material is a special semiconductor material structure. It is formed by periodically alternating the growth of two or more semiconductor materials with different band gap widths and electron affinities in a manner with a very high lattice matching through a carefully designed process. This unique combination gives superlattice materials a series of unique physical and chemical properties. Subsequently, Kasper's team successfully prepared In2O3(ZnO) n (n=2, 5, 7) superlattice structure. In 1988, Cannard and Tilley proposed that the structure is actually composed of alternating growth of In-O layers and In / Zn-O layers. This new theory was subsequently confirmed by Kimizuka's team, and they found that InGaO3(ZnO) n andInFeO3(ZnO) n Similar structural phenomena have been found in materials such as ZnO and InMO3. Based on these findings, scientists refer to these materials as homologous compounds InMO3(ZnO). n (where M represents trivalent metal elements such as In, Ga, Al and Fe, and n represents the period of layered stacking). This series of discoveries and studies not only deepened our understanding of the structure of superlattice materials, but also provided an important theoretical basis for future material design and application. As the research deepened, the general molecular formula of superlattice materials changed from InMO3(ZnO) to n Gradually extended to M2O3(ZnO) nGenerally speaking, researchers prefer to choose binary elements such as In series for co-doping to form superlattice materials with unique properties, while there are relatively few studies on doping of transition elements. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a one-dimensional ScGa3(ZnO) n A superlattice nanowire and a preparation method thereof are provided to solve the problem of lack of transition element-doped superlattice nanowires in the prior art.
[0005] The technical solution of the present invention to solve the above technical problems is as follows: a one-dimensional ScGa3(ZnO) n Superlattice nanowire and preparation method thereof, comprising the following steps:
[0006] (1) ScGa-ZnO precursor solution: dissolve a zinc source, a scandium source and a gallium source in an organic solvent, add a stabilizer, stir at 80-90° C. for 45-70 min, and age at room temperature in the dark for 30-48 h to obtain a ScGa-ZnO precursor solution;
[0007] (2) ScGa-ZnO precursor solution coating ZnO nanowires: The Si substrate on which the ZnO nanowires are grown is tilted at an angle of 25-35°, and the ZnO nanowires are coated with the ScGa-ZnO precursor solution prepared in step (1) by capillary action, and then dried at 180-200° C. for 25-35 min to obtain ScGa-ZnO precursor solution coated ZnO nanowires;
[0008] (3) Heat treatment: The ScGa-ZnO precursor solution obtained in step (2) is coated with ZnO nanowires and heat treated at 1100-1200°C for 10-15 min to obtain one-dimensional ScGa3(ZnO) n Superlattice nanowires.
[0009] On the basis of the above technical solution, the present invention can also be improved as follows:
[0010] Furthermore, in step (1), the element molar ratio of Zn, Sc and Ga in the zinc source, scandium source and gallium source is 1:1:1.
[0011] The beneficial effect of adopting the above further technical solution is that the interaction and reaction between them are more balanced, thereby reducing the chemical instability caused by fluctuations in element ratios and ensuring the stability and repeatability of the reaction.
[0012] Furthermore, in step (1), the zinc source is Zn(CH3COO)2·2H2O; the scandium source is Sc(NO3)3·2H2O; and the gallium source is Ga(NO3)3·2H2O.
[0013] The beneficial effect of adopting the above further technical solution is that these salt compounds usually have a higher purity and can reduce the impact of impurities on the performance of the nanowires.
[0014] Furthermore, in step (1), the volume ratio of the organic solvent to the stabilizer is 1000-5000:1.
[0015] Furthermore, in step (1), the volume ratio of the organic solvent to the stabilizer is 1000:1.
[0016] The beneficial effect of adopting the above further technical solution is that the addition of the stabilizer can significantly improve the stability of the nanowires in the organic solvent, prevent them from agglomerating or precipitating, thereby ensuring the uniform dispersion and stability of the nanowires during the preparation process. Since the amount of stabilizer added is relatively small (volume ratio is 1:1000), it will not introduce too many impurities. This helps to maintain the high purity of the nanowires and reduce the impact of impurities on the performance of the nanowires.
[0017] Furthermore, in step (1), the organic solvent is ethylene glycol methyl ether.
[0018] The beneficial effect of adopting the above further technical solution is that ethylene glycol methyl ether is a relatively stable compound, which is not easily oxidized by oxygen in the air and is not easily decomposed by heat. This stability ensures that the solution is not easily deteriorated during the preparation of superlattice nanowires, which is conducive to maintaining the stability of the reaction system.
[0019] Furthermore, in step (1), the stabilizer is ethanolamine.
[0020] The beneficial effects of adopting the above further technical solution are: ethanolamine, as a stabilizer, has good stability and easy adsorption. When added to chemicals, it can stabilize the molecular structure of the chemicals by forming hydrogen bonds, van der Waals forces, etc., to prevent adverse reactions such as oxidation and volatilization.
[0021] Furthermore, in step (1), the stirring is carried out in a constant temperature magnetic stirrer in a sealed environment at a rotation speed of 150-250 r / min.
[0022] The beneficial effects of adopting the above further technical solution are: the constant temperature magnetic stirrer has the characteristics of high sensitivity and strong controllability, which can ensure the stability of temperature during the preparation process. Stirring within the speed range of 150-250r / min can ensure that the substances in the solution are evenly mixed.
[0023] Furthermore, in step (1), the concentration of the ScGa-ZnO precursor solution is 0.002-0.05 mol / L.
[0024] Furthermore, in step (1), the concentration of the ScGa-ZnO precursor solution is 0.01-0.05 mol / L.
[0025] Furthermore, in step (1), the concentration of the ScGa-ZnO precursor solution is 0.01 mol / L.
[0026] The beneficial effect of adopting the above further technical solution is that the ScGa-ZnO precursor solution with a concentration of 0.01 mol / L ensures a stable supply of solutes during the experiment, which is conducive to the precise synthesis of nanomaterials, thereby obtaining products with specific structures and properties.
[0027] Furthermore, in step (2), the ScGa-ZnO precursor solution is dripped onto the inclined Si substrate, and coating is achieved by solution diffusion.
[0028] The beneficial effect of adopting the above further technical solution is that due to the use of an inclined Si substrate, the solution naturally diffuses under the action of gravity, which helps to achieve a more uniform and efficient coating effect. This method can reduce the unevenness and material waste during the coating process.
[0029] Furthermore, in step (3), heat treatment is performed in an air atmosphere.
[0030] The beneficial effects of adopting the above further technical solution are: heat treatment in air atmosphere helps decompose organic matter and oxidize metal ions in the precursor solution, promotes the formation and crystallization of ScGa-ZnO nanostructures, and improves the purity and crystallinity of the nanostructures, thereby enhancing their physical and chemical properties.
[0031] The present invention also provides a one-dimensional ScGa3(ZnO) prepared by the above method n Superlattice nanowires.
[0032] Further, one-dimensional ScGa3(ZnO) n The diameter of the superlattice nanowires is 50-90nm and the length is 10-50μm.
[0033] The present invention also provides a one-dimensional ScGa3(ZnO) n Application of superlattice nanowires in the preparation of semiconductor materials.
[0034] The present invention has the following beneficial effects:
[0035] 1. The present invention successfully prepared one-dimensional ScGa3(ZnO) through a three-step high-temperature solid-state diffusion method. nNew superlattice nanowire material. With the incorporation of Sc atoms, the lattice constant of the system becomes slightly larger, the bond length becomes longer, the volume becomes larger, and the total energy of the system increases. This change changes the electronic structure of ZnO, thereby affecting its physical and chemical properties. Due to the changes in the electronic structure and optical properties of Sc-doped ZnO, as well as the improvement of corrosion resistance, the present invention has potential application value in the fields of light-emitting devices, liquid crystal displays, gas sensors, etc.
[0036] 2. Based on the characteristics of the material itself, the present invention adopts high-temperature solid-state diffusion technology to cleverly integrate trace amounts of Sc and Ga elements into the ZnO one-dimensional material, thereby successfully constructing a superlattice structure while maintaining the main basic properties of the ZnO nanowires. In this process, Sc and Ga elements are finely modified on the surface of the ZnO nanowires in the form of approximate atomic chains, giving the material new properties and functions.
[0037] 3. After XRD (X-ray diffraction) testing, no compounds such as scandium oxide and gallium oxide were detected in the ScGa-ZnO superlattice nanowires. This result fully proves that the prepared superlattice nanowires have high purity characteristics and no significant impurities. Through in-depth analysis of XPS (X-ray photoelectron spectroscopy) characterization technology, we found that it has a high concentration of oxygen vacancies, which is closely and inseparable from the formation of superlattices. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the SEM image (5 μm) of ZnO nanowires in Comparative Example 1;
[0039] Figure 2 This is the SEM image of ZnO nanowires in Comparative Example 1 (500 nm);
[0040] Figure 3 STEM image of ZnO nanowires of Comparative Example 1 Figure 1 (50nm);
[0041] Figure 4 STEM image of ZnO nanowires of Comparative Example 1 Figure 2 (50nm);
[0042] Figure 5 This is the SEM (5 μm) image of the superlattice nanowire of Example 1;
[0043] Figure 6 is the SEM image of the superlattice nanowire of Example 1 (100 nm);
[0044] Figure 7 The superlattice nanowire STEM of Example 1 Figure 1 (50nm);
[0045] Figure 8 The superlattice nanowire STEM of Example 1 Figure 2 (50nm);
[0046] Fig. 9 XRD diagrams of nanowires in Example 1 and Comparative Example 1;
[0047] Fig.10 for Fig. 9 A local magnified view of the ZnO (100) peak position;
[0048] Fig.11 for Fig. 9 A local enlarged view of the ZnO (002) peak position;
[0049] Fig.12 for Fig. 9 A local enlarged view of the ZnO (110) peak position;
[0050] Fig.13 This is the XPS image (Zn 2p) of the superlattice nanowire of Example 1;
[0051] Fig.14 This is the XPS image of the superlattice nanowire of Example 1 (Ga 2p3);
[0052] Fig.15 This is the XPS image (Sc 2p) of the superlattice nanowire of Example 1;
[0053] Fig.16 This is the XPS image of the superlattice nanowire of Example 1 (O 1s). DETAILED DESCRIPTION
[0054] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples are only used to explain the present invention and are not used to limit the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0055] Embodiment 1:
[0056] A one-dimensional ScGa3(ZnO) n The superlattice nanowire, the preparation method thereof comprises the following steps:
[0057] (1) ScGa-ZnO precursor solution: accurately weigh 0.0219 g of zinc source (Zn(CH3COO)2·2H2O), 0.0231 g of scandium source (Sc(NO3)3·2H2O) and 0.0256 g of gallium source (Ga(NO3)3·2H2O) using an analytical balance, place them in a clean beaker, add 10 mL of organic solvent ethylene glycol methyl ether, add 10 μL of stabilizer ethanolamine, place a magnetic stirring rotor in the beaker, and seal the beaker with high-temperature sealing glue and tape to ensure that no liquid splashes during stirring. Then, place the sealed beaker in a constant temperature magnetic stirrer, stir for 60 min at 70°C and 200 r / min, and age at room temperature in the dark for 24 h to obtain a ScGa-ZnO precursor solution with a concentration of 0.01 mol / L;
[0058] (2) ScGa-ZnO precursor solution coating ZnO nanowires: Place the Si substrate with ZnO nanowires grown on a glass slide tilted at 30°, use a pipette to accurately absorb 20 μL of the ScGa-ZnO precursor solution prepared in step (1), and drip the solution at the upper edge of the Si substrate sample to ensure that the solution gradually diffuses and completely infiltrates the ZnO nanowires. The ScGa-ZnO precursor solution coats the ZnO nanowires through capillary action. Dry in an oven at 150°C for 20 min to remove the solvent in the precursor solution on the surface of the nanowires, ensure that the precursor can firmly adhere to the surface of the nanowires, and obtain ScGa-ZnO precursor solution coated ZnO nanowires;
[0059] (3) Heat treatment: The ScGa-ZnO precursor solution obtained in step (2) is coated with ZnO nanowires and placed in a porcelain boat, which is then placed in a tube furnace and heat treated at 900°C in an air atmosphere for 15 min, so that the Sc and Ga elements in the precursor enter the ZnO interior through solid-state diffusion and replace Zn atoms to obtain one-dimensional ScGa3(ZnO) n Superlattice nanowires.
[0060] Embodiment 2:
[0061] A one-dimensional ScGa3(ZnO) n The superlattice nanowire, the preparation method thereof comprises the following steps:
[0062] (1) ScGa-ZnO precursor solution: accurately weigh 0.0219 g of zinc source (Zn(CH3COO)2·2H2O), 0.0231 g of scandium source (Sc(NO3)3·2H2O) and 0.0256 g of gallium source (Ga(NO3)3·2H2O) using an analytical balance, place them in a clean beaker, add 50 mL of organic solvent ethylene glycol methyl ether, add 10 μL of stabilizer ethanolamine, place a magnetic stirring rotor in the beaker, and seal the beaker with high-temperature sealing glue and tape to ensure that no liquid splashes during stirring. Then, place the sealed beaker in a constant temperature magnetic stirrer, stir for 45 min at 80°C and 200 r / min, and age at room temperature in the dark for 30 h to obtain a ScGa-ZnO precursor solution with a concentration of 0.002 mol / L;
[0063] (2) ScGa-ZnO precursor solution coating ZnO nanowires: Place the Si substrate with ZnO nanowires grown on a glass slide tilted at 25°, use a pipette to accurately absorb 20 μL of the ScGa-ZnO precursor solution prepared in step (1), and drip the solution at the upper edge of the Si substrate sample to ensure that the solution gradually diffuses and completely infiltrates the ZnO nanowires. The ScGa-ZnO precursor solution coats the ZnO nanowires through capillary action. Dry in an oven at 180°C for 35 min to remove the solvent in the precursor solution on the surface of the nanowires, ensure that the precursor can firmly adhere to the surface of the nanowires, and obtain ScGa-ZnO precursor solution coated ZnO nanowires;
[0064] (3) Heat treatment: The ScGa-ZnO precursor solution obtained in step (2) is coated with ZnO nanowires and placed in a porcelain boat, which is then placed in a tube furnace and heat treated for 15 min at 1100°C in an air atmosphere, so that the Sc and Ga elements in the precursor enter the ZnO interior through solid-state diffusion and replace Zn atoms to obtain one-dimensional ScGa3(ZnO) n Superlattice nanowires.
[0065] Embodiment 3:
[0066] A one-dimensional ScGa3(ZnO) n The superlattice nanowire, the preparation method thereof comprises the following steps:
[0067] (1) ScGa-ZnO precursor solution: accurately weigh 0.1095 g of zinc source (Zn(CH3COO)2·2H2O), 0.1155 g of scandium source (Sc(NO3)3·2H2O) and 0.1280 g of gallium source (Ga(NO3)3·2H2O) using an analytical balance, place them in a clean beaker, add 10 mL of organic solvent ethylene glycol methyl ether, add 10 μL of stabilizer ethanolamine, place a magnetic stirring rotor in the beaker, and seal the beaker with high-temperature sealing glue and tape to ensure that no liquid splashes during stirring. Then, place the sealed beaker in a constant temperature magnetic stirrer, stir for 45 min at 90°C and 200 r / min, and age at room temperature in the dark for 48 h to obtain a ScGa-ZnO precursor solution with a concentration of 0.05 mol / L;
[0068] (2) ScGa-ZnO precursor solution coating ZnO nanowires: Place the Si substrate with ZnO nanowires grown on a glass slide tilted at 35°, use a pipette to accurately absorb 20 μL of the ScGa-ZnO precursor solution prepared in step (1), and drip the solution at the upper edge of the Si substrate sample to ensure that the solution gradually diffuses and completely infiltrates the ZnO nanowires. The ScGa-ZnO precursor solution coats the ZnO nanowires through capillary action. Dry in an oven at 200°C for 25 min to remove the solvent in the precursor solution on the surface of the nanowires, ensure that the precursor can firmly adhere to the surface of the nanowires, and obtain ScGa-ZnO precursor solution coated ZnO nanowires;
[0069] (3) Heat treatment: The ScGa-ZnO precursor solution obtained in step (2) is coated with ZnO nanowires and placed in a porcelain boat, which is then placed in a tube furnace and heat treated at 1200°C in an air atmosphere for 10 min, so that the Sc and Ga elements in the precursor enter the ZnO interior through solid-state diffusion and replace Zn atoms to obtain one-dimensional ScGa3(ZnO) n Superlattice nanowires.
[0070] Comparative Example 1:
[0071] Unheat-treated ZnO nanowires.
[0072] Test example
[0073] 1. SEM / STEM Characterization
[0074] The one-dimensional ScGa3(ZnO) prepared in Example 1 n The superlattice nanowires and the untreated ZnO nanowires of Comparative Example 1 were subjected to SEM and STEM tests. Figure 1-8 .
[0075] Depend on Figure 1-8 It is known that in Figure 6 We can clearly see the etching marks, which reveal subtle changes in the material surface. Figure 7-8 They show a clear light-dark-light stripe pattern. This unique light-dark structure is not accidental, but is caused by the contrast difference caused by elements of different atomic masses. These differences not only reveal the microstructure inside the material, but also provide important clues for us to understand its properties. The formation of this structure is due to the special arrangement of Ga atoms in the Sc-O and Ga / Zn-O layers, which effectively reduces the strain energy of the material and provides favorable conditions for the doping process. The discovery of this structure not only enriches our understanding of the microstructure of the material, but also provides new ideas for us to design more efficient doping strategies.
[0076] Through precise ruler measurement, the average diameter of ZnO nanowires changed significantly after heat treatment, from the initial about 50nm to 73nm after 15 minutes of heat treatment at 900℃. This change not only reflects the effect of heat treatment on the material morphology, but also provides an important basis for us to understand its structural evolution. At the same time, in the doping experiment, we observed the co-doping phenomenon of Sc and Ga elements. Sc element, with its smaller strain energy and energy advantages, successfully brought in Ga element, forming Sc-Ga co-doped Sc-Ga-Zn-O superlattice structure. This discovery not only verifies our theoretical prediction, but also provides us with a new strategy for preparing high-performance superlattice materials.
[0077] Based on the above observations and analysis, we can conclude that after Sc-Ga element co-doping, a layered structure with alternating bright-dark-bright and clear boundaries is formed in the material. This structure conforms to the typical characteristics of a superlattice, which not only shows the orderly arrangement of elements inside the material, but also indicates its unique physical and chemical properties. Therefore, as trivalent elements, Sc and Ga have a higher degree of adaptability and are easier to enter the octahedral structure, thereby promoting the formation and stability of the superlattice structure.
[0078] 2. XRD Characterization
[0079] The one-dimensional ScGa3(ZnO) prepared in Example 1 was n The superlattice nanowires and the pure ZnO nanowires of Comparative Example 1 were subjected to XRD (X-ray diffraction) testing, and the results are shown in Figure 9-12 .
[0080] Depend on Fig. 9 It can be seen that no Sc2O3 and Ga2O3 impurity phases were found in the ScGa-ZnO superlattice nanowires.
[0081] In the context of X-ray diffraction, when the optical path difference (defined as 2dsinθ) is exactly equal to an integer multiple of the incident X-ray wavelength (λ), the diffraction effect of the crystal plane will be significantly enhanced. This physical phenomenon satisfies the famous Bragg equation: 2dsinθ = nλ. Among them, d represents the spacing between the crystal planes, θ is the angle between the incident X-ray and the crystal plane, λ is the wavelength of the X-ray, and n is the reflection order. The Bragg equation is the key condition for the diffraction phenomenon of X-rays inside the crystal. In the X-ray diffraction pattern (XRD pattern), the horizontal coordinate 2θ is closely related to the crystal plane spacing of the measured substance.
[0082] Depend on Figure 9-12 It can be seen that the diffraction angles corresponding to the (002) and (110) crystal planes have a slight shift after doping, with the shift angle being about 0.02°. This change directly reflects that the interplanar spacing of the ZnO crystal has changed after doping, thus proving that the incorporation of elements has indeed caused lattice distortion. The reason why no angle shift was found on the (100) crystal plane is mainly because the type and concentration of the doping element have a significant effect on the XRD shift. Smaller doping atoms and lower doping concentrations may cause smaller XRD shifts, or they may not be enough to be detected.
[0083] 3. XPS Characterization
[0084] The one-dimensional ScGa3(ZnO)n superlattice nanowires prepared in Example 1 were subjected to XPS (X-ray photoelectron spectroscopy) detection. The results are shown in Figure 13-16 .
[0085] During the data analysis, we calibrated all binding energies using 284.8 eV of C1s as the benchmark.
[0086] Depend on Figure 13-16 It can be seen that there are Zn, O, Sc, and Ga elements in the one-dimensional ScGa3(ZnO)n superlattice nanowire. 3 / 2 and Zn-2p 1 / 2 The peaks are located at 1021.6eV and 1044.7eV respectively, with a difference of 23.1eV, which is close to the standard value of 22.97eV. An asymmetric shape appears in the O-1s spectrum. After peak separation, two peaks can be obtained, located at 530.3eV and 532.1eV respectively; the peak of 530.7eV comes from O-1s in the sample, while the peak of 532.1eV comes from O-1s in CO or C=O in the air. The two Sc-2p peaks are located at 401.8eV and 406.4eV respectively, corresponding to Sc-2p 3 / 2 and Sc-2p 1 / 2 , the energy difference is 4.6eV, which is close to the standard value of 4.9eV. 3 / 2 and Ga-2p1 / 2 , and the peaks are at 1117.9 and 1144.8 eV, respectively, with an energy difference of 26.9 eV, which is highly consistent with the standard value of 26.9 eV. These findings reveal a certain concentration of oxygen vacancies in Sc-Ga-Zn-O nanowires, and Sc and Ga are successfully introduced into the nanowires to form Sc-O bonds and Ga-O bonds, respectively, which may have an important impact on the physical and chemical properties of one-dimensional ScGa3(ZnO)n superlattice nanowires.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A one-dimensional ScGa3(ZnO) n A method for preparing superlattice nanowires, characterized in that: The following steps are involved: (1) ScGa-ZnO precursor solution: dissolve a zinc source, a scandium source and a gallium source in an organic solvent, add a stabilizer, stir at 80-90° C. for 45-70 min, and age at room temperature in the dark for 30-48 h to obtain a ScGa-ZnO precursor solution; (2) ScGa-ZnO precursor solution coating ZnO nanowires: The Si substrate on which the ZnO nanowires are grown is tilted at an angle of 25-35°, and the ZnO nanowires are coated with the ScGa-ZnO precursor solution prepared in step (1) by capillary action, and then dried at 180-200° C. for 25-35 min to obtain ScGa-ZnO precursor solution coated ZnO nanowires; (3) Heat treatment: The ScGa-ZnO precursor solution obtained in step (2) is coated with ZnO nanowires and heat treated at 1100-1200°C for 10-15 min to obtain one-dimensional ScGa3(ZnO) n Superlattice nanowires.
2. The one-dimensional ScGa3(ZnO) according to claim 1 n A method for preparing superlattice nanowires, characterized in that: In step (1), the element molar ratio of Zn, Sc and Ga in the zinc source, scandium source and gallium source is 1:1:
1.
3. The one-dimensional ScGa3(ZnO) according to claim 1 n A method for preparing superlattice nanowires, characterized in that: In step (1), the zinc source is Zn(CH3COO)2·2H2O; the scandium source is Sc(NO3)3·2H2O; and the gallium source is Ga(NO3)3·2H2O.
4. The one-dimensional ScGa3(ZnO) according to claim 1 n A method for preparing superlattice nanowires, characterized in that: In step (1), the volume ratio of the organic solvent to the stabilizer is 1000-5000:
1.
5. The one-dimensional ScGa3(ZnO) according to claim 1 n A method for preparing superlattice nanowires, characterized in that: In step (1), the concentration of the ScGa-ZnO precursor solution is 0.002-0.05 mol / L.
6. The one-dimensional ScGa3(ZnO) according to claim 1 n A method for preparing superlattice nanowires, characterized in that: In step (2), the ScGa-ZnO precursor solution is dripped onto the inclined Si substrate, and coating is achieved by solution diffusion.
7. The one-dimensional ScGa3(ZnO) according to claim 1 n A method for preparing superlattice nanowires, characterized in that: In step (3), heat treatment is performed in an air atmosphere.
8. The one-dimensional ScGa3(ZnO) according to claims 1-7 n One-dimensional ScGa3(ZnO) prepared by the preparation method of superlattice nanowires n Superlattice nanowires.
9. The one-dimensional ScGa3(ZnO) according to claim 8 n Superlattice nanowire, characterized in that The one-dimensional ScGa3(ZnO) n The diameter of the superlattice nanowires is 50-90nm and the length is 10-50μm.
10. The one-dimensional ScGa3(ZnO) according to claim 8 n Application of superlattice nanowires in the preparation of semiconductor materials.
Citation Information
Patent Citations
Fibrous ZnO nanowire growing on ZnO nanowire array and preparation method thereof
CN104264131A
Preparation method of ultrathin zinc oxide nanosheet electrode
CN108483483A
Preparation method of IGZO superlattice nanoparticles
CN109095497A
Preparation method of IGZO superlattice nanowire array
CN109264769A
Two-dimensional InGa3 (ZnO) m superlattice nanobelt and preparation method thereof
CN117038712A
